Factors Influencing the Formation of Settlement Patterns in the Batu Meja Area, RT 005 RW 002 - Julius Denis Waatwahan; Mohammad Amin Lasaiba; Ferdinand Salomo Leuwol (Jurnal Pendidikan Geografi Unpatti, 2024)
This study aims to analyze the factors influencing the settlement pattern formation in Batu Meja RT 005 RW 002. The primary issue is the steep topography and limited infrastructure, such as roads, water, and waste disposal systems, which affect settlement patterns and community accessibility. The research employs a descriptive qualitative method, collecting data through observation, interviews, and documentation to explore residents' perceptions of their settlement patterns. The findings reveal that, despite challenges related to difficult access, the community has made independent efforts to build simple infrastructure like footpaths and retaining walls (tallit) to mitigate landslide risks. The study concludes that topography and infrastructure significantly impact the settlement pattern in this area. The implications suggest that government intervention is necessary to provide better infrastructure and spatial planning policies that support safe and sustainable settlements.